Comparative Analysis of Biomass-Based Adsorbents for Heavy Metal Ion Removal - Pertiwi, Beta Cahaya; Firginia, Noni; Satyasyauqi, Muhammad Fauzan; Matovanni, Maudy Pratiwi Novia (UPN Veteran Jatim, 2025)
This study investigates the adsorption capabilities of various biomass-based adsorbents for the removal of heavy metal ions from industrial wastewater. This research focusses on the comparative effectiveness of chemical and steam activation methods. Steam-activated adsorbents derived from wine sector waste exhibited a maximum adsorption capacity for Pb²⁺ ions of 399 mg/g. Adsorbents derived from walnut shells and chemically activated with HNO₃ ions exhibited a maximum adsorption capacity of 204.08 mg/g for Cu²⁺ ions. Steam-activated spruce sawdust adsorbents achieved optimal adsorption of Fe²⁺ ions at a capacity of 329 mg/g. The adsorption capacity for Cd⁺ ions was determined to be 116 mg/g, achieved through microwave-assisted steam activation of palm kernel shell-based adsorbents. The research emphasizes the necessity of selecting appropriate activation techniques based on specific heavy metal ions and the desired adsorption properties. Additionally, there is a necessity for further investigation into the processes of pore structure development and their impact on adsorption effectiveness. The findings suggest that developing adsorbent from biomass waste represents a sustainable and effective method for reducing heavy metal contamination in industrial wastewater, thereby advancing environmental protection and resource efficiency.